PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN YANG DIMODERASI CORPORATE SOCIAL RESPONSIBILITY - Itsnaini, Hafidah Mufliha; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis meant to examine the influenceof profitability to the firm value, solvency of the firm value, the CSR to the firm value, the profitability to the firm value with the CSR as the moderating variable and the solvency to the firm value with the CSR as the moderating variable.The population is all mining companieswhich are listed in Indonesia Stock Exchange in 2011-2015 periods and the samples are 39 companies. The samplecollection technique has been done by purposive sampling method which results 12 samples in 2011-2015 periods. The data is the secondary data which has been obtainedby using documentation technique which consists of the 2011-2015annual reportof mining companies. The data analysis has been carried out by using multiple regression analysis.The result of this research indicates that profitability has positive influenceto the firm value, solvency has negativeinfluence to the firm value, the CSR has positive influenceto the firm value, the result of residual test shows that the CSR disclosure cannot moderate the correlation between profitability and firm value, and the result residual test shows that CSR disclosurecan moderate the correlation between solvency and firm value.Keywords: Profitability, solvency, Tobins Q, corporate social responsibility disclosure.